‘Ceremonious ape!’: creaturely poetics and anthropomorphic acts - Anderton, Joseph (Routledge, 2015)
Creaturely life partly refers to the nostalgia for a former human status hinged on normative, established forms of signification. In response, creaturely poetics is concerned with ways of composing the accentuated material and categorical vulnerability that ensues. In "Ceremonious Ape!": Creaturely Poetics and Anthropomorphic Acts, Joseph Anderton expounds a creaturely poetics of the stage, describing an approach to the spectacle, concreteness and shared spaces of performance that emphasise the bodily conditions shared by human and nonhuman animals alike. With reference to Samuel Beckett’s Waiting for Godot and Catastrophe, Teevan’s adaptation Kafka’s Monkey and Vesturport’s Metamorphosis, I trace a double process of dehumanisation and re-humanisation as the plays variously enact the fall of human language, logic and freedom, evoking creaturely life only to convey anthropomorphic performances of the ruined human model. Vestiges of supposedly exclusive human characteristics lingering in this performance mode are, I contend, an anthropomorphic act. Through metatheatrical and antitheatrical strategies, as well as themes attentive to physical vulnerability, the plays dissolve human specificity and plunge the characters into an unsettled, liminal condition that gestures towards the presence and precariousness of all living beings.